Teknologi Informasi Dalam Pengelolaan Keuangan Publik: Implikasi Terhadap Transparansi Dan Akuntabilitas - faesal gibran; resbi irmayani; sayyid ahmad walmukmin; Muhammad Budi Utama (Journal of Public Sector Financial Management, 2026)
This article looks at how information technology (IT) is used in public financial management to improve transparency and accountability. With the background of administrative reforms that focus on good governance, this research highlights the role of IT in digitalizing financial systems, such as real-time record-keeping and digital payments, which can strengthen administrative efficiency and oversight. However, implementing IT often faces challenges like limited human resources, infrastructure, and cultural resistance within bureaucracy. The study uses a qualitative approach with a literature review method, analyzing 50 documents from 2000 to 2025 through inductive thematic analysis. The results show three main themes: IT as a tool for integration and efficiency; challenges in implementation within organizational dynamics; and positive implications for transparency and accountability, although these depend on the institutional context. The discussion interprets these findings holistically, emphasizing the need for cultural adaptation and oversight mechanisms for optimal results. Theoretically, this research strengthens the use of qualitative approaches in public financial studies; practically, it encourages staff training and inclusive policies; and recommends integrating IT with independent audits to build public trust. The limitations of the method can be addressed through mixed-method research in the future.